miR-1338-5p Modulates Growth Hormone Secretion and Glucose Utilization by Regulating ghitm in Genetically Improved Farmed Tilapia (GIFT, Oreochromis niloticus) - Qiang, Jun; Bao, Jing Wen; Li, Hong Xia; Chen, De Ju; He, Jie; Tao, Yi Fan; Xu, Pao (Frontiers in Physiology, 2017)
MicroRNAs (miRNAs) are endogenous, non-coding small RNA molecules about 22nt in length, which could regulate the expressions of target genes and participate in growth and development of organisms. Genetically improved farmed tilapia (GIFT, Oreochromis niloticus) is an important economic freshwater species in China and the growth performance is one of the main breeding indicators. Growth hormone inducible transmembrane protein (ghitm) plays an important role in growth and development of both mammals and invertebrates; however, little studies have been reported on fish. Our previous experiments indicated that miR-1338-5p expression may be negatively correlated with ghitm expression. In this study, we firstly used qRT-PCR and northern blot to verify the expression of miR-1338-5p and ghitm, and determined the binding site of miR-1338-5p in the ghitm 3'-untranslated region (UTR) by luciferase reporter assay. Secondly, juveniles GIFT injected with miR-1338-5p antagomir were used to analyze the regulatory function of the miR-1338-5p–ghitm pair in vivo. The results showed that the ghitm 3'-UTR was complementary to the 5' 2-8-nt site of miR-1338-5p. Inhibition of miR-1338-5p promoted ghitm expression in the pituitary and liver of GIFT. ghitm could interfere in the growth hormone (Gh)–gh receptor (Ghr)–insulin-like growth factor (Igf) signaling pathway by competing with the ghr1 for combination with Gh, and then reduce the growth of GIFT. Moreover, the reduction of Gh in serum may regulate insulin secretion and result in the increasing sugar and fat storage in serum and liver. Our results suggest that miR-1338-5p participates in the growth and development of GIFT through the regulation of ghitm, which provides theoretical support for the study of the fish growth mechanism.